Visualize and Learn Sorting Algorithms in Data Structure Subject in a Game-based Learning - Lim, Wee Han; Cai, Yiyu; Yao, Dezhong; Cao, Qi (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
The Data Structure subject is an essential Computer Science subject. Sorting algorithms are important topics in Data Structure where students are expected to learn how various sorting algorithms work and their time complexities. Some sorting algorithms may easily cause confusions to novice students, as they usually find it challenging to understand and memorize these algorithms. There is a need to find a means of technology enhanced learning to improve the learning process of students. Game based learning is a pedagogy where students learn through game playing. This mode of learning could effectively engage students to focus on the learning topics more efficiently. The study uses a sorting algorithm serious game to allow students to learn four types of sorting algorithms: Bubble sort, Selection sort, Insertion sort and Quick sort. The students would carry out self-directed learning lecture materials in the serious game, followed by refreshing their learning using a visualizer, and lastly reinforce their learning through playing a sorting serious game. Two groups of students participate in the experiment, a control group and an experiment group. The experiment group that sues the sorting algorithm games achieves better results, compared to the control group who learns without the serious game. Game-based learning provides a positive learning experience to the students that could improve the learning effectiveness. Coupled with technology such as VR headsets as a future upgrade, it would be a niche factor that would create an immersive learning experience to engage the students and enhance their learning in a virtual environment.